Examining intervention mechanisms of action using mediation analysis within a randomised trial of a whole-school health intervention. Issue 5 (5th February 2019) - Bonell, Chris; Allen, Elizabeth; Opondo, Charles; Warren, Emily; Elbourne, Diana Ruth; Sturgess, Joanna; Bevilacqua, Leonardo; McGowan, Jennifer; Mathiot, Anne; Viner, Russell M
Abstract : Background: Interventions to modify school environments are effective in promoting young people's health across outcomes, but mechanisms are poorly understood. We assessed mediation in a trial of the Learning Together intervention, building on the recent publication of results of effectiveness for reducing bullying and benefits across secondary outcomes and generally good implementation fidelity. Methods: Within a cluster-randomised trial involving 40 English schools, we examined student-reported and staff-reported school climate and student-reported involvement with delinquent peers at 24-month and 36-month follow-up, assessing the reliability of measures and whether these mediated health outcomes at a final follow-up. Results: Response rates and reliability were good for student-reported but not staff-reported measures. The intervention increased student-reported but not staff-reported-positive school climate but, like effects on student health outcomes, these manifested only at a final follow-up. The intervention reduced student-reported contact with delinquent peers at an interim follow-up. Student-reported potential mediators measured at the interim follow-up were associated with most health outcomes at the final follow-up. Adjustment for student-reported school climate and contact with delinquent peers at the interim follow-up did not reduce the associations between trial arm and our health outcomes. Conclusion: Despite being constrained by imperfect measures and by the late manifestation of impacts on student-reported school climate undermining ability to assess mediation, our study for the first time provides tentative evidence that mediation of intervention effects via improved climate and disengagement from delinquent peers is plausible. Our study provides the first evidence from a trial that whole-school interventions may work by modifying school environments and student relationships. Trial registration number: ISRCTN10751359 .